Predicting financial distress in hospitality companies listed on the IDX (2019-2023) with the alt man z-score model - Dengang, Andreas; Oktafiani, Fida (Institute of Computer Science (IOCS), 2024)
The impact of the global pandemic on the hospitality industry has been significant, with notable fluctuations in room occupancy rates during the pandemic. This undoubtedly has a significant impact on the revenue of hospitality companies. In order to ascertain the financial resilience of hospitality service companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023, researchers conducted a study entitled 'Predicting Financial Distress in Hospitality Companies Listed on the IDX (2019-2023) with the Altman Z-Score Model'. This study employed a descriptive approach with quantitative methods, utilising 10 samples of hospitality service companies listed on the Indonesia Stock Exchange. The findings of this study indicate that the impact of the pandemic has had a significant effect on the financial health of hospitality companies. This is demonstrated by the findings of the Altman Z-Score model, which was used to predict the likelihood of bankruptcy for hospitality companies. The results demonstrate that the proportion of companies experiencing financial distress increased from 10% in 2019 to 40% in 2023. In 2019, financial distress was observed in only 10% of companies, while in 2020, the onset of the pandemic in Indonesia led to an increase to 20%. This figure continued to rise, reaching 40% by 2023.